On hyperbolic relaxation problems - Yong, Wen-An; Jäger, Willi (Analysis and Numerics for Conservation Laws, 2005)
This report summarizes our works on hyperbolic systems of first-order partial differential equations with source terms. We discuss the introduction of our structural stability and entropy dissipation conditions for initial or initial-boundary value problems. For initial value problems, several systematic results are reviewed. These include the non-existence of (linearly stable) relaxation approximations to non-strongly hyperbolic systems of equations, the justification of the formal zero relaxation limit, the existence of relaxation shock profiles, and the existence of global smooth solutions for balance laws.